Payback time - Deuker, Carl (Houghton Mifflin Harcourt, 2012)
Overweight, somewhat timid Mitch reluctantly agrees to be the sports reporter for the Lincoln High newspaper because he's determined to be a writer, but he senses a real story in Angel, a talented football player who refuses to stand out on the field--or to discuss his past